The association of codon 392 polymorphism in ESR2 gene with breast cancer in Iran - Abbasi, Sakineh; Kalbasi, Samira (Kurdistan Journal of Applied Research, 2019)
Epidemiological studies revealed that the pattern of age onset of breast cancer in the Middle East region differ from those in Caucasians. Therefore, genomic data for ESR2 (ER-?) is of the value in the clinical setting for that ethnic group and the aim of the current investigation is investigated whether polymorphisms in the ER-? gene are associated with breast cancer risk among Iranian women. The coding sequence in Exon 7 at ESR2 gene was looking for any variation among the Iranian breast cancer women by SSCP-PCR method. In codon 392 of exon 7, showed a silent SNP (silent single nucleotide polymorphism). The frequency of allele G in codon 392 (CTC ? CTG was found only in cases (5.7%). We also found that allele G in codon 392 (C1176G) had direct association with development of lymph node metastasis in breast cancer. The current results suggest that ESR2 SNP in exon 7, codon 392 is associated with various aspects of breast cancer in Iran. ESR2 gene structure determination, in presurgical evaluation, might be a useful marker in predicting familial breast cancer and metastasis in LN.